Gavage of D-Ribose induces Aβ-like deposits, Tau hyperphosphorylation as well as memory loss and anxiety-like behavior in mice - Wu, Beibei (Oncotarget, 2015)
In addition to D-Glucose, D-Ribose is also abnormally elevated in the urine of type 2 diabetic patients, establishing a positive correlation between the concentration of uric D-Ribose and the severity of diabetes. Intraperitoneal injection of D-Ribose causes memory loss and brain inflammation in mice. To simulate a chronic progression of age-related cognitive impairment, we orally administered D-Ribose by gavage at both a low and high dose to 8 week-old male C57BL/6J mice daily for a total of 6 months, followed by behavioral, histological and biochemical analysis. We found that long-term oral administration of D-Ribose impairs spatial learning and memory, accompanied by anxiety-like behavior. Tau was hyperphosphorylated at AT8, S396, S214 and T181 in the brain. Aβ-like deposition was also found in the hippocampus for the high dose group. D-Glucose-gavaged mice did not show significant memory loss and anxiety-like behavior under the same experimental conditions. These results demonstrate that a long-term oral administration of D-Ribose not only induces memory loss with anxiety-like behavior, but also elevates Aβ-like deposition and Tau hyperphosphorylation, presenting D-Ribose-gavaged mouse as a model for age-related cognitive impairment and diabetic encephalopathy.